2011
DOI: 10.3168/jds.2010-3984
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the addition of direct-fed microbials and glycerol to the diet of lactating dairy cows on milk yield and apparent efficiency of yield

Abstract: A study was conducted to evaluate the effects of a direct-fed microbial (M) and dietary glycerol (G) on milk yield, efficiency of yield, and nutrient digestibility during hot weather. Sixty Holstein cows averaging 120 d in milk (DIM) and 36.2 kg/d of milk were used in a 12-wk 2×2 factorial design trial from June through September 2008. Cows were fed a common diet during the 2-wk standardization period and were blocked by milk yield, DIM, parity, and dry matter intake. Diets were based on corn and ryegrass sila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 28 publications
6
59
3
Order By: Relevance
“…Therefore, glycerine may be a good source of energy for high-yielding cows, especially in the transition period when the cow has a limited feed intake capacity and its addition to the ration may positively affect feed intake, blood metabolic profile and hepatic lipid metabolism, limit the energy deficit after calving, and prevent metabolic disorders. Boyd et al (2011) reported that dietary glycerol may improve performance and efficiency in high-yielding dairy cows. Similarly, data presented by Carvalho et al (2011) indicate that glycerol can be recommended to replace maize in rations fed to transition dairy cows up to about 11% of the pre-and post-partum ration DM, based on the lack of detrimental effects on feed intake, milk production or milk composition.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, glycerine may be a good source of energy for high-yielding cows, especially in the transition period when the cow has a limited feed intake capacity and its addition to the ration may positively affect feed intake, blood metabolic profile and hepatic lipid metabolism, limit the energy deficit after calving, and prevent metabolic disorders. Boyd et al (2011) reported that dietary glycerol may improve performance and efficiency in high-yielding dairy cows. Similarly, data presented by Carvalho et al (2011) indicate that glycerol can be recommended to replace maize in rations fed to transition dairy cows up to about 11% of the pre-and post-partum ration DM, based on the lack of detrimental effects on feed intake, milk production or milk composition.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, the supplementation of lactating dairy cows with a DFM product containing a mixture of L. acidophilus and P. freudenreichii improved milk and protein yield, and apparent digestibility of crude protein, neutral detergent fiber, and acid detergent fiber, so that it could be used to enhance the performance of cows subject to heat stress during hot weather [155].…”
Section: Dairy Propionibacteria: Less Conventional Probiotics To Imprmentioning
confidence: 99%
“…Because lactating Holstein cows require more energy for lactation, LDH enzyme activity may be increased, in many tissues, as compared to non-lactating cows. In addition, rumen bacterial fermentation, due to lactate-producing organism such as Lactobacillus acidophilus could also affect LDH value in cows [29].…”
Section: Discussionmentioning
confidence: 99%